2009
DOI: 10.3329/jhpn.v27i2.3327
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Obstetric Care in Public-sector Facilities and Constraints to Implementing Emergency Obstetric Care Services: Evidence from High- and Low-performing Districts of Bangladesh

Abstract: This study explored the quality of obstetric care in public-sector facilities and the constraints to programming comprehensive essential obstetric care (EOC) services in rural areas of Khulna and Sylhet divisions, relatively high- and low-performing areas of Bangladesh respectively. Quality was explored by physically inspecting all public-sector EOC facilities and the constraints through in-depth interviews with public-sector programme managers and service providers. Distribution of the functional EOC faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
102
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(114 citation statements)
references
References 17 publications
8
102
0
4
Order By: Relevance
“…First, signal functions for assessment of EmNC in this study did not include provision of prophylactic antibiotics to the mother in case of preterm or prolonged premature rupture of membranes, which may limit the ability to compare the findings with other studies. In addition, the number of basic EmONC facilities has fluctuated over the years, 21,32,53,62 possibly due to supply failure or inability to deliver the service (e.g., lack of drugs or absence of a provider, and renovations of maternity wards). Studies that enable a better understanding of this gap will help to guide future preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, signal functions for assessment of EmNC in this study did not include provision of prophylactic antibiotics to the mother in case of preterm or prolonged premature rupture of membranes, which may limit the ability to compare the findings with other studies. In addition, the number of basic EmONC facilities has fluctuated over the years, 21,32,53,62 possibly due to supply failure or inability to deliver the service (e.g., lack of drugs or absence of a provider, and renovations of maternity wards). Studies that enable a better understanding of this gap will help to guide future preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that lack of job openings in government health facilities for nurses was a common barrier to obstetric care programs in rural Bangladesh. 62 The most common limitations to recruitment and retaining health staff include the lack of desire to work in remote rural areas, and low morale among staff working in public facilities that are often overcrowded and underequipped. 63 The lack of trained staff has been suggested as one of the major obstacles in ensuring high-quality neonatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the quality of obstetric care in hospitals in Bangladesh, but Research there is some evidence of substandard care within public facilities. 22,23 There are substantial constraints on human resources, and some staffing positions may be left unfilled. The costs of care to patients are high; patients invariably have to buy some medicines -particularly for obstetric surgery -and evidence-based practices, such as the use of magnesium sulfate or the partograph, are far from universal.…”
Section: Discussionmentioning
confidence: 99%
“…The worst quality was found at upazila level. 6 The study (Table 11) found that half of the health personnel interviewed did not have any training on baby delivery. Only three had training and two of them were in NGOs.…”
Section: Quality Of Carementioning
confidence: 99%